2011
DOI: 10.1007/s13402-011-0028-6
|View full text |Cite
|
Sign up to set email alerts
|

EBV-infection in cardiac and non-cardiac gastric adenocarcinomas is associated with promoter methylation of p16, p14 and APC, but not hMLH1

Abstract: Hypermethylation of tumor suppressor genes is significantly more frequent in EBV-associated GC compared to EBV-negative GC. Our data add new insights to the role of EBV in gastric carcinogenesis and underline that EBV associated GC comprise a distinct molecular-pathologic as well as a distinct clinicopathological entity of GC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 35 publications
3
21
0
6
Order By: Relevance
“…As previously reported [33], all EBV-positive tumors exhibited extreme CIMP, distinct from that in the MSI subtype [10] (CDKN2A promoter hypermethylation versus MLH1 hypermethylation) [34]. Furthermore, in concordance with prior data [35,36], the study revealed a strong predilection for PIK3CA mutation in EBV positive tumors, with nonsilent PIK3CA mutations found in 80% of this subgroup (P < 0.001), that could be targeted using PI(3)-kinase inhibition.…”
Section: Molecular Classiication Of Gastric Cancers By "The Cancer Gesupporting
confidence: 88%
See 1 more Smart Citation
“…As previously reported [33], all EBV-positive tumors exhibited extreme CIMP, distinct from that in the MSI subtype [10] (CDKN2A promoter hypermethylation versus MLH1 hypermethylation) [34]. Furthermore, in concordance with prior data [35,36], the study revealed a strong predilection for PIK3CA mutation in EBV positive tumors, with nonsilent PIK3CA mutations found in 80% of this subgroup (P < 0.001), that could be targeted using PI(3)-kinase inhibition.…”
Section: Molecular Classiication Of Gastric Cancers By "The Cancer Gesupporting
confidence: 88%
“…CIN tumors were mostly located in the gastroesophageal junction/ cardia, whereas most of the EBV-positive tumors were located in the gastric fundus or body. Genomically, stable tumors were diagnosed at an earlier age compared to MSI tumors; most EBV-positive cases were male (81%), in concordance with previous results [32].As previously reported [33], all EBV-positive tumors exhibited extreme CIMP, distinct from that in the MSI subtype [10] (CDKN2A promoter hypermethylation versus MLH1 hypermethylation) [34]. Furthermore, in concordance with prior data [35,36], the study revealed a strong predilection for PIK3CA mutation in EBV positive tumors, with nonsilent PIK3CA mutations found in 80% of this subgroup (P < 0.001), that could be targeted using PI(3)-kinase inhibition.…”
supporting
confidence: 89%
“…7 Increasing evidences showed significantly higher frequencies of promoter cytosine-guanine dinucleotide (CpG) methylation of tumor suppressor genes (eg, p14, p15, p16, p73, APC, E-cadherin, CDH1, and PTEN) in EBV-associated gastric cancer than EBV-negative gastric cancer. [8][9][10] EBVdriven aberrant promoter methylation will lead to the transcriptional silence of tumor suppressors in EBV-associated gastric cancer, thus resulting in uncontrolled cell expansive growth. 11 Aberrant promoter methylation contributes to human gastric carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…This led to the hypothesis, that Lynch syndrome may have caused gastric cancer associated with renal cancer in our cohort. In addition, we searched for EBV in cancer tissues, particularly since EBV is associated with hypermethylation of tumorsuppressor genes known to be involved gastric cancer (34).…”
Section: Discussionmentioning
confidence: 99%